Study on Excreta Disposal Methods and the Occurrence of Faeco-oral Diseases in Owerri-North L.G.A, Imo State - Chidinma Miriam Chikwe; Chike C Okereke; Chikere I C Ebirim; Sally N O Ibe; Rita O Chukwu; Emmanuel U Nwakwasi (Archives of Community Medicine and Public Health - Peertechz Publications, 2020)
Introduction: Access to excreta disposal facility (sanitary toilet) is a necessary human right of everybody and the fundamental sign of sustainable development. Children and adults regularly suffer from diarrhea and typhoid fever which are diseases that are spread mostly through faeco-oral route. The general objective of this study was to determine the excreta disposal methods and the occurrence of faeco-oral diseases in Owerri-north L.G.A., Imo State. Methods: A cross-sectional study design was performed for this study. The sample size was calculated using Yamane formula as such the sample size was 400. Multi-stage sampling method was used in selecting communities that participated in the study. Data was collected with the aid of a structured questionnaire. Data analysis was done using Statistical Package for Social Science (SPSS) version 21. Data collected was presented using descriptive statistics such as frequencies and percentages; the hypotheses were tested using chi-square (x2) statistic at ≤0.05 level of significance. Result: The result revealed that of the 400 households sampled; 83.3% uses water closet/ pour-flush latrine, 11.0% uses pit latrine, 3.8% uses VIP latrine, 1.0% practices wrap and throw methods, 0.5% uses bucket latrine while 0.2% practices both digging in the compound and sand fill/ open defecation respectively. Frequently reported faeco-oral diseases include; Typhoid fever (34.0%), Diarrhea (20.3%) and Dysentery (4.8%). The study also revealed that there was a significant relationship between faeco-oral diseases suffered by members of the households and the type of the toilet system used by the household (X2=96.2702, P<0.002).  Conclusion: Although most households in this study area use water closet/pour flush latrine, which is the most convenient and environmental friendly excreta disposal method yet majority of them suffer from faeco-oral diseases. Therefore, households should practice hygienic use of their various excreta disposal facilities in order to prevent occurrence of faeco-oral diseases.